Estudo comparativo da prevalência de cárie em pré-escolares de instituições de ensino da rede pública com e sem assistência odontológica, do município de Bauru-SP - Bergamini, Cristiane Berriel Joaquim (2015)
Dental decay is a widely known disease, but it needs constant research for a better understanding of its distribution in the populations so that it is possible to plan and perform preventive and curative actions. Thus, the aim of this study was to evaluate and compare the prevalence of dental decay in children with an average age of five years, students from municipal public preschools from Bauru-SP, with and without dental care, and to describe the profile of the families of the students surveyed. The study was carried out with a population of 511 children enrolled in 14 Municipal Early Childhood Education Schools (EMEIs) after the approval of the Research Ethics Committee and the authorization by the child's parents or guardians who signed the Informed Consent. To evaluate the decays, we used the DMFT index. The students’ parents participated in the research answering a questionnaire about the access to dental services, level of information on dental decay and socioeconomic status. The results showed a low prevalence of dental decay, with an average DMFT index of 1.64 and 57.3% of children free of dental decay, with no significant difference between schools with and without dental care (Mann-Whitney test and the Chi-Square test, respectively, p>0.05). For schools with dental care, the DMFT index was 1.65, and 60.2% of the children were free of dental decay while, for schools without dental care, the DMFT index was 1.63 and 54.1% of the children were free of dental care. We found a smaller percentage of decayed teeth and a higher percentage of teeth restored for the children of the EMEIs with a dentist, showing that there was a statistical difference for the components of the DMFT index between the two types of schools studied (Chi-Square Test, p<0.05). The group of preschools with a dentist showed to have more access to dental services, although most of the responsible adults reported some difficulty in taking their children to dental treatment at Health Centers. We verified low levels of parental information about dental decay and most of the families had a monthly income of up to 3 minimum wages. Therefore, the dental care in the EMEIs did not influence the prevalence of tooth decay in children; however, it significantly reduced dental treatment needs.